Efektivitas Pembelajaran Ekonomi Berbantuan Media Digital Dalam Meningkatkan Pemahaman Kreativitas Siswa XI.9 SMA Negeri 1 Cilimus - Syafitri, Syifa Nurul; Jubaidah, Indah; Yana, Enceng; Putri, Dian Permana (Jurnal Ilmiah Global Education, 2025)
The purpose of this study is to examine the effectiveness of digital media-assisted economic learning using Wordwall-based gamification in enhancing students’ creative understanding in class XI.9 of SMA Negeri 1 Cilimus. This research employed a quasi-experimental method with a one-group pre-test–post-test design, involving a total of 18 student participants. Data were collected through direct observation, semi-structured interviews with the teacher and four students, and visual documentation. The data were analyzed using the N-Gain test and the Wilcoxon Signed Ranks Test, as the data did not meet the assumptions of normal distribution. The findings revealed a significant difference between the pre-test and post-test results (Asymp. Significance 2-tailed = 0.01 < 0.05), indicating that the use of digital media effectively improved student learning outcomes. Qualitative data further showed increased student engagement, creativity, and motivation during the learning process. These findings support the conclusion that gamified digital media can serve as an innovative solution to foster enjoyable, interactive, and meaningful learning experiences in economic education.